Comparison of a novel aluminum lactate-based with an aluminum chloride-based antiperspirant in excessive axillary and inguinal perspiration: first randomized controlled trial - Lütgerath, Constantin; Weiß, Christel; Faulhaber, Jörg; Karsai, Syrus (Journal der Deutschen Dermatologischen Gesellschaft, 2022)
Background Topical aluminum salts are a commonly used remedy for excessive axillary perspiration. To the contrary, less is known about their anhidrotic potential in the groin. This study sought to compare the anhidrotic efficacy and tolerability of an aluminum chloride-based antiperspirant to an innovative aluminum lactate-based antiperspirant in healthy study participants presenting with excessive axillary and inguinal perspiration. Participants and Methods Fifty participants were enrolled in this open open-labeled, randomized, controlled trial. Following a baseline assessment, efficacy was analyzed at two time points throughout the study period by means of four physiological parameters (pH value, transepidermal water loss, gravimetric analysis, Minor test) and two questionnaires (Dermatology Life Quality Index, Hyperhidrosis Disease Severity Scale). Tolerability was evaluated via symptom diaries. Results Both study preparations were comparably effective in reducing axillary and inguinal perspiration and exhibited increasing effectiveness over time. In both treatment regions, the aluminum lactate-based antiperspirant had a more favorable tolerability profile than the aluminum chloride-based antiperspirant. Conclusions Due to its comparable efficacy and - most noticeably in the groin - superior tolerability, this study supports the use of topical aluminum lactate as a first-line option to control excessive axillary and inguinal perspiration.
Gesehen am 08.07.2024